EXPLORING CONSUMER INTEREST, PRICE, AND PERCEPTION IN COFFEE PURCHASING DECISIONS AT BELIKOPI SIDOARJO - Yunita Wulandari; Mochamad Rizal Yulianto; Rizky Eka Febriansah (STIE PGRI Dewantara Jombang, 2026)
This study was conducted to analyze the effect of purchase interest, price, and consumer perception on purchasing decisions at Kedai Belikopi Sidoarjo. The research method used was a quantitative approach with the help of Tolls SmartPLS version 3.29. Data collection was carried out by distributing questionnaires to Kedai Belikopi consumers, with a total of 96 respondents. From the test results, it can be seen that purchase interest has a positive and significant effect on purchasing decisions, with a T-count > the T table value of 1.98 and 4.700, and a P-Value of 0.00 below 0.05. Price has a positive and significant effect on purchasing decisions with a T-Statistic value of 2.559 and a P-Value of 0.011. Consumer perception does not affect purchasing decisions with a T-statistic value of 0.059 and a P-value of 0.953.